2023
DOI: 10.1530/ec-22-0504
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and testing for growth hormone deficiency across the ages: a global view of the accuracy, caveats, and cut-offs for diagnosis

Abstract: Growth hormone deficiency (GHD) is a clinical syndrome that can manifest either as isolated or associated with additional pituitary hormone deficiencies. Although diminished height velocity and short stature are useful and important clinical markers to consider testing for GHD in children, the signs and symptoms of GHD are not always so apparent in adults. Quality of life and metabolic health are often impacted in patients with GHD; thus, making an accurate diagnosis is important so that appropriate GH replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 175 publications
(346 reference statements)
1
6
0
Order By: Relevance
“…GSTs are useful tools in diagnosing GHD, especially in those without obvious causes of GHD such as intracranial tumors or irradiation ( 9 ). We acknowledge that several studies of various GH stimulation test protocols in different parts of the world have suggested different GH peak cut offs ranging from 5 to 10 ng/dL ( 31 ). But for all practical purposes the current agreed GH cut off in the United States remains to be 10 ng/dL ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…GSTs are useful tools in diagnosing GHD, especially in those without obvious causes of GHD such as intracranial tumors or irradiation ( 9 ). We acknowledge that several studies of various GH stimulation test protocols in different parts of the world have suggested different GH peak cut offs ranging from 5 to 10 ng/dL ( 31 ). But for all practical purposes the current agreed GH cut off in the United States remains to be 10 ng/dL ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether lower cutoffs should be used with the newer, more sensitive, 2-site assays has not been definitively determined. According to newer studies, which used a sensitive, immunochemiluminescent, 2-site assay, the values of 5.1 μg/L for the ITT and 4.1 μg/L for the GH-releasing hormone–arginine test had sufficient specificity and sensitivity for the diagnosis of GHD [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients reported common stimulation test related side effects, such as facial flushing, nausea, headache or transient dysgeusia [20].…”
Section: Ghrh/arginine Testmentioning
confidence: 95%